Escribanos enfrentados en el Yucatán de la segunda mitad del siglo XVI: Conflicting Notaries in the second half of 16th century Yucatan - Mardegan, Riccardo (2022)
Although the importance in the daily life of Spanish (and in other terms also Indigenous) population, the notarial profession in Yucatán never received the deserved attention by researchers. In the present work, an attempt will be made to reconstruct the events concerning two Yucatecan notaries in relation to the constitution of their own archives during the second half of the 16th century, also analysing the dialectical relationship that put them in conflict for the management of imperial and local power and the arguments used to defend their own jurisdiction.